2022
DOI: 10.1021/acs.molpharmaceut.1c00918
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Activity of EGFR Targeted Polymeric Micelles Delivering a New Inhibitor of DNA Repair to Orthotopic Colorectal Cancer Xenografts with Metastasis

Abstract: The disruption of polynucleotide kinase/phosphatase (PNKP) in colorectal cancer (CRC) cells deficient in phosphatase and tensin homolog (PTEN) is expected to lead to the loss of cell viability by a process known as synthetic lethality. In previous studies, we have reported on the encapsulation of a novel inhibitor of PNKP, namely, A83B4C63, in polymeric micelles and its activity in slowing the growth of PTEN-deficient CRC cells as well as subcutaneous xenografts. In this study, to enhance drug delivery and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In another study, the outer shell of the nanomicelles was grafted with dodecapeptide GE11 to exploit EGFR so as to ameliorate deep tumor tissue internalization and retention. 28 Fabricated nanomicelles comprising-polyethylene oxide- block -polycaprolactone (PEO/ b /PCL) amphiphilic copolymer and PEO/ block /(α-benzyl carboxylate-ε-caprolactone)(PEO/ b /PBCL) amphiphilic copolymer were prepared via ring-opening polymerization. GE11-grafted nanomicelles were then conjugated with NIR dye Cy5.5 via azide–alkyne click chemistry 34 to form GE11-PEO/ b /PCL-Cy5.5 and GE11-PEO/ b /PBCL-Cy5.5 nanomicelles.…”
Section: Polymeric Micelles For Targeting Different Receptorsmentioning
confidence: 99%
“…In another study, the outer shell of the nanomicelles was grafted with dodecapeptide GE11 to exploit EGFR so as to ameliorate deep tumor tissue internalization and retention. 28 Fabricated nanomicelles comprising-polyethylene oxide- block -polycaprolactone (PEO/ b /PCL) amphiphilic copolymer and PEO/ block /(α-benzyl carboxylate-ε-caprolactone)(PEO/ b /PBCL) amphiphilic copolymer were prepared via ring-opening polymerization. GE11-grafted nanomicelles were then conjugated with NIR dye Cy5.5 via azide–alkyne click chemistry 34 to form GE11-PEO/ b /PCL-Cy5.5 and GE11-PEO/ b /PBCL-Cy5.5 nanomicelles.…”
Section: Polymeric Micelles For Targeting Different Receptorsmentioning
confidence: 99%
“…Another study led by de Paiva et al on modifying the surface of polymeric micelles to improve the delivery and specificity of a new inhibitor of polynucleotide kinase/phosphatase (PNKP) to colorectal cancer (CRC) tumors [ 152 ]. To achieve this, a peptide called GE11 was used to target the epidermal growth factor receptor (EGFR) that is commonly overexpressed in about 70% of CRC tumors.…”
Section: Strategies To Target Pcl-based Drug Delivery Carriersmentioning
confidence: 99%
“…These results suggest the potential benefit of EGFR-targeted polymeric micellar formulations as monotherapeutics for aggressive and metastatic CRC tumors. However, they also highlight the need for the development of EGFR ligands with improved physiological stability and binding to EGFR [152]. Li et al have developed a cutting-edge solution to deliver doxorubicin and cypate to cancer cells [143].…”
Section: Active Targetingmentioning
confidence: 99%
“…In normal cells, EGFR expression ranges from 4 × 10 4 to 10 5 receptors per cell [ 36 ], whereas epidermoid cell carcinoma lines (A431) express up to 2 × 10 6 EGFR molecules per cell [ 37 ]. Because of these properties, EGFR has been widely used for EGFR-mediated delivery of various medical agents, as demonstrated for nanoformulated photosensitizers [ 38 ], anticancer drugs [ 39 ], polyplexes [ 40 ], and other compounds. For example, Kim and others have shown that coupling cetuximab, an antibody against EGFR, to the liposomal surface enhances delivery of siRNA to target mice with SK-OV-3 tumor xenografts.…”
Section: Introductionmentioning
confidence: 99%